Pengaruh pendidikan kewirausahaan, kompetensi profesional guru, dan efikasi diri terhadap minat wirausaha siswa - Aji Noercahyo; Sudarno; Feri Setyowibowo (Jurnal Pendidikan Ekonomi (JUPE), 2026)
Unemployment among vocational school graduates remained the highest in August 2023. This issue is one of the problems addressed in this study. The study aims to determine the influence of entrepreneurship education, teachers' professional competence, and self-efficacy on the entrepreneurial interest of students at SMK Muhammadiyah 3 Gemolong. This study employs a quantitative research design, with the study population consisting of 156 students in grades XI and XII at SMK Muhammadiyah 3 Gemolong for the 2024/2025 academic year, and a sample size of 113 students. The sampling technique used is simple random sampling. Data was collected using a questionnaire via Google Forms. This study uses multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results of the study indicate that entrepreneurship education, teachers' professional competence, and self-efficacy influence students' entrepreneurial interest at SMK Muhammadiyah 3 Gemolong. The findings of this study can serve as additional knowledge regarding students' entrepreneurial interest in relation to entrepreneurship education, teachers' professional competence, and self-efficacy.